A case of pulmonary hamartoma with distinctive histopathological features: A discussion of its differential diagnosis and histogenesis. (14th November 2014) - Okudela, Koji; Umeda, Shigeaki; Otara, Misa; Honda, Emi; Ohmori, Takahiro; Tajari, Michihiko; Kameda, Yoichi; Ohashi, Kenichi
<x xml:space="preserve">Abstract</x> We herein describe a case of a benign pulmonary tumor with distinctive histopathological features. A 55‐year‐old Japanese male presented with a well‐demarcated tumor in the left upper lobe of his lung, which gradually increased in size from 18 to 21 mm over 24 months. The resected tumor consisted of an epithelial component of compact irregular glands and mesenchymal component of fascicles between the glands. The differentiation of pneumocytes and smooth muscle cells was immunohistochemically detected in the epithelial component and the mesenchymal component, respectively. No mitosis, necrosis, bleeding, or invasion was observed. A histopathologic diagnosis of fibroleiomyomatous hamartoma was made. We also review previously reported tumors with similar histopathological features and discuss their differential diagnosis and histogenesis.